Cause of Death After Surgical Aortic Valve Replacement: SWEDEHEART Observational Study - Natalie Glaser (Wiley, 2021)
Background Prior studies showed that life expectancy in patients who underwent surgical aortic valve replacement (AVR) was lower than in the general population. Explanations for this shorter life expectancy are unknown. The aim of this nationwide, observational cohort study was to investigate the cause‐specific death following surgical AVR. Methods and Results We included 33 018 patients who underwent primary surgical AVR in Sweden between 1997 and 2018, with or without coronary artery bypass grafting. The SWEDEHEART (Swedish Web‐System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies) register and other national health‐data registers were used to obtain and characterize the study cohort and to identify causes of death, categorized as cardiovascular mortality, cancer mortality, or other causes of death. The relative risks for cause‐specific mortality in patients who underwent AVR compared with the general population are presented as standardized mortality ratios. During a mean follow‐up period of 7.3 years (maximum 22.0 years), 14 237 (43%) patients died. The cumulative incidence of death from cardiovascular, cancer‐related, or other causes was 23.5%, 8.3%, and 11.6%, respectively, at 10 years, and 42.8%, 12.8%, and 23.8%, respectively, at 20 years. Standardized mortality ratios for cardiovascular, cancer‐related, and other causes of death were 1.79 (95% CI, 1.75–1.83), 1.00 (95% CI, 0.97–1.04), and 1.08 (95% CI, 1.05–1.12), respectively. Conclusions We found that life expectancy following AVR was lower than in the general population. Lower survival after AVR was explained by an increased relative risk of cardiovascular death. Future studies should focus on the role of earlier surgery in patients with asymptomatic aortic stenosis and on optimizing treatment and follow‐up after AVR. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02276950.